Prevalence and Maternal Effects of Hypothyroidism in Pregnancy - Ferdousi, Mahmuda Ashrafi; Baki, Abdullah Al (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Thyroid disorders are among the common endocrine problems in pregnant women. It is now well established that not only overt but subclinical thyroid dysfunction also has adverse effects on maternal and fetal outcome. There are few data from Bangladesh about the prevalence of thyroid dysfunction in pregnancy. With this background, this study aims to find prevalence of thyroid dysfunction in pregnancy and its impact on obstetrical outcome. Materials and methods: It is an observational study done in a Combined Military Hospital (CMH) Chattogram during the period from February to December 2020 on 130 hypothyroid mothers to observe maternal effects of hypothyroidism. Patients were collected as per inclusion and exclusion criteria after informed written consent. Data was compiled and analyzed and presented. Results: Among 1148 total patients,1018(89%) were normal and 130(11%) were diagnosed as hypothyroid.Among all the patients, 35% patientsare from inside the Chattogram and 65% are from outside. Among 130 hypothyroid cases age range revealed 20-45 years and 20 -30 years age group were 82(63.07%), 30-40 years age group was 40(30.76%) and >40 years age group were 8(6.15%). Primigravida was 48(36.92%) cases and multigravida was 82(63.08%) cases, anemia was present in 40(30.76%) cases, 10(7.69%) patients had hypertension, GDM and DM was found in 20(15.38%)and 3(2.30%) cases respectively, preconception hypothyroidism was found in 10(7.69%) and on Levothyroxine during ANC was 120(92.30%).Among all, 63(48.46%) cases were underwent vaginal delivery and 67(51.53%) cases underwent cesarean section. Untreated and irregular treatment in hypothyroidism are associated with pregnancy complications like spontaneous miscarriage 40(30.76%), maternal anaemia 55(42.30%), pre-eclampsia 4(3.07%), pre term birth 16(12.30%), postpartum haemorrhage 3(2.30%). Conclusion: Hypothyroidism is a common clinical condition during pregnancy and it causes variable pregnancy outcome Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 18-21